How Does Social Embeddedness Affect Farmers’ Adoption Behavior of Low-Carbon Agricultural Technology? Evidence From Jiangsu Province, China - Zheng, Huawei; Ma, Jing; Yao, Zhaoyu; Hu, Feng (Frontiers in Environmental Science, 2022)
Agricultural carbon emissions, which are the second largest source of greenhouse gas emissions in China, not only place great pressure on emission reduction, but also seriously affect food security and sustainable development of agriculture. As farmers are the direct users of cultivated land and the main adopters of agricultural technology, their adoption behavior of low-carbon agricultural technology directly determines its promotion and subsequent emissions reduction. It is of great theoretical and practical significance to analyze farmers’ adoption behavior of low-carbon agricultural technology and their influencing factors. Based on social embeddedness theory and the survey data of 688 farmers in Jiangsu Province, this study applied a logistic model to analyze the impact of government support, farmers’ cognition, social capital, personal characteristics, and family characteristics on farmers' adoption behavior of low-carbon agricultural technology. The results showed that: (1) only 58.72% of farmers have adopted such a technology, which needs to be further improved; (2) government support, and farmers’ cognition had significantly positive influences on farmers' adoption behavior; (3) social capital is an important factor affecting farmers' adoption decisions, where social trust, networks and norms play a significant role in promoting the adoption of low-carbon agricultural technology; (4) Party membership and household-contracted farmland area also had positive influences on farmers' adoption behavior of low-carbon technology. Therefore, to continue developing low-carbon agriculture, it is recommended to further strengthen government support, raise the price of low-carbon agricultural products, strengthen environmental supervision, and build a social embedded environment according to local conditions; Further improve farmers' social trust, enrich social networks, improve social norms, and give full play to the guiding and exemplary role of social capital; Additionally, it is also recommended to reinforce education and training to raise farmers' awareness regarding low-carbon agricultural technology, thereby guiding them to actively adopt these technologies.